Recontextualizing Islamic Education Through Cultural Resilience: Perspectives of Ulama and Customary Leaders in Mandailing Natal - Sulaiman, Muhammad Arib; Nisoh, Anan; Anshori, Irfan; Kahfi, Al; Mohamoud, Mohamed Esse (Al Irsyad: Jurnal Studi Islam, 2025)
The main issue lies in the lack of empirical studies on the dual leadership practices of ulama and traditional leaders in the management of Islamic education in Mandailing Natal, particularly concerning the integration of local cultural values. This study explores the dynamics of Islamic education management in Mandailing Natal, Indonesia, emphasising the integration of local cultural values and traditional leadership. Employing a qualitative ethnographic case study approach, data were collected through in-depth interviews, participatory observation, and institutional document analysis. The findings reveal a contextual and culturally-rooted model of Islamic education management in Mandailing Natal, where ulama function as religious leaders and customary authorities. Integrating indigenous values such as dalihan na tolu, hasuhutan, and marsialap ari into the educational system positions pesantren and madrasah as cultural preservation and character education centres. The collective leadership and participatory local curriculum demonstrate an organic and resilient management model, offering a culturally grounded alternative to the often centralised and homogenised Islamic education system. Conclusion: Integrating local culture into the governance of pesantren and madrasah enhances institutional relevance and provides a new perspective on educational leadership that merges religious authority with cultural legitimacy.